An owner questionnaire and cohort study on equine wounds and their management - Birnie, Richard (2021)
Traumatic wounds have been described as the second most common reason for out-of-hours emergency veterinary visits in the horse. Sequelae of wound injury can pose a risk to life and return to pre-athletic function and incur significant treatment costs. Existing literature on equine wound healing and management has reported several factors to impact on wound outcome however, this body of research consists predominantly of retrospective studies specific to referral horse populations, expert opinion, and extrapolations from human medicine. The lack of high-quality evidence reported in the literature, particularly relating to concepts and current habits of owner attitudes towards wound management, served as the impetus for this project. The aim of this project was to generate primary evidence on the healing and outcome of wounds in horses, including documenting the attitudes and current habits of owners towards wound management and to perform descriptive and statistical analysis of the presenting signs, treatment and outcomes of these injuries. Data was captured through the use of an online questionnaire and prospective cohort study.